Skilled labor supply, IT-based technical change and job instability - Luc Behaghel; Julie Moschion (Institute for the Study of Labor (IZA), 2012)
We provide empirical evidence on the impact of IT diffusion on the stability of employment relationships. We document the evolution of different components of job instability over a panel of 348 local labor markets in France, from the mid-1970s to the early 2000s. Although workers in more educated local labor markets adopt IT faster, they do not experience any increase in job instability. More specifically, we find no evidence that the diffusion of IT increases job-to-job transitions, and we find that it tends to reduce transitions to non-employment among high-school dropouts. Overall, the evidence goes against the view that the diffusion of IT has spurred job instability. Combining local labor market variations with firm data, we argue that these findings can be explained by French firms' strong reliance on training and internal promotion strategies in order to meet the new skills requirement associated with IT diffusion.
Keywords: J23; J24; J41; 330; technical change; labor turnover; skill bias; job security; internal labor markets; Informationstechnik; Innovationsdiffusion; Hochqualifizierte Arbeitskräfte; Technischer Fortschritt; Arbeitsplatzsicherung; Frankreich